Global Ramifications of Dust and Sandstorm Microbiota. (29th June 2018) - Behzad, Hayedeh; Mineta, Katsuhiko; Gojobori, Takashi
Abstract: Dust and sandstorm events inject substantial quantities of foreign microorganisms into global ecosystems, with the ability to impact distant environments. The majority of these microorganisms originate from deserts and drylands where the soil is laden with highly stress-resistant microbes capable of thriving under extreme environmental conditions, and a substantial portion of them survive long journeys through the atmosphere. This large-scale transmission of highly resilient alien microbial contaminants raises concerns with regards to the invasion of sensitive and/or pristine sink environments, and to human health—concerns exacerbated by increases in the rate of desertification. Further increases in the transport of dust-associated microbiota could extend the spread of foreign microbes to new ecosystems, increase their load in present sink environments, disrupt ecosystem balance, and potentially introduce new pathogens. Our present understanding of these microorganisms, their phylogenic affiliations and functional significance, is insufficient to determine their impact. The purpose of this review is to provide an overview of available data regarding dust and sandstorm microbiota and their potential ramifications on human and ecosystem health. We conclude by discussing current gaps in dust and sandstorm microbiota research, and the need for collaborative studies involving high-resolution meta-omic approaches in conjunction with extensive ecological time-series studies to advance the field towards an improved and sufficient understanding of these invisible atmospheric travelers and their global ramifications.